Molecular biology of glucose-6-phosphate dehydrogenase and UDP-glucuronosyltransferase 1A1 in the development of neonatal unconjugated hyperbilirubinemia - Yi-Li Hung; Pi-Feng Chang; Ching-Shan Huang (Pediatrics and Neonatology)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency and variants of the UDP-glucuronosyltransferase 1A1 (UGT1A1) gene are the most common genetic causes of neonatal unconjugated hyperbilirubinemia (NUH). In this review, we searched PubMed for articles on the genetic causes of NUH published before December 31, 2022, and analyzed the data. On the basis of the results, we reached eight conclusions: (1) 37 mutations of the G6PD gene are associated with NUH; (2) the clinical manifestation of G6PD deficiency depends not only on ethnicity but also on the molecular mechanisms underlying the deficiency (and thus its severity); (3) of mutations in the UGT1A1 gene, homozygous c.−53A(TA)6TAA > A(TA)7TAA is the main cause of NUH in Caucasians and Africans, whereas homozygous c.211G > A is the main genetic cause of NUH in East Asians; (4) in Indonesian neonates, homozygous c.−3279T > G is the most common cause of NUH development, and neither c.−53 A(TA)6TAA > A(TA)7TAA nor c.211G > A causes it; (5) in breast-fed East Asian neonates, the TA7 repeat variant of the UGT1A1 gene protects against the development of NUH; (6) G6PD deficiency combined with homozygous c.211G > A variation of the UGT1A1 gene increases the risk of severe NUH; (7) in Pakistani and Caucasian patients with Crigler–Najjar syndrome type 2 (CN-2), point mutations of the UGT1A1 gene are widely distributed and frequently occur with variation at nucleotide −53, whereas in Asian patients with CN-2, compound homozygous variations in the coding region are frequently observed; and (8) records of G6PD deficiency and UGT1A1 variation status for a neonate offer useful pharmacogenomic information that can aid long-term care. These results indicate that timely diagnosis of NUH through molecular tests is crucial and that early initiation of treatment for the neonates and educational programs for their parents improves outcomes.